Peran Penting Sinematografi dalam Pendidikan pada Era Teknologi Informasi dan Komunikasi - Miyarso, Estu (Fakultas Ilmu Pendidikan UNY, 2011)
This paper discusses the important role of cinematography as a discipline of applied science. Linkages digital cinematography with the development of multimedia as a form of information and communication technologies. Also describes the implementation of cinematography in the field of educational technology or learning today. Key Words: Cinematography in The Field of Educational, Information and Communication Technologies Times